FRI0452 A 26-Week Study of Efficacy and Safety of Delayed-Release Prednisone in Newly-Diagnosed Cases of GIANT Cell Arteritis: an Interim Analysis. (10th June 2014) - Raine, C.; Maw, W.W.; Williams, M.; Gayford, D.; Mapplebeck, S.; Borg, F.A.; Mackerness, C.; Hirst, D.; Dasgupta, B.
Abstract : Background: Lodotra is a modified-release formulation of prednisone taken at 22:00pm, allowing the active drug to be released 4–6 hours later, synchronous with the nocturnal circadian peak of the inflammatory cytokine interleukin-6. Given high relapse rates and adverse events with standard glucocorticoids (GC) in giant cell arteritis (GCA), an exploratory study of efficacy and safety of modified0release prednisone in patients with newly diagnosed GCA was performed. We report here on an interim analysis. Objectives: To evaluate the efficacy and safety of delayed-release prednisone in patients with newly diagnosed GCA. Methods: This 26 week feasibility study was designed using a randomised open protocol and a blinded evaluator, and compared modified-release (MR) prednisone versus standard of care immediate-release (IR) prednisone in patients with newly diagnosed GCA. Sixteen cases with an unequivocal clinical and laboratory picture of new GCA, either meeting ACR criteria or with typical ischaemic features were recruited. All cases underwent temporal artery biopsy (TAB). All cases were treated with initial high dose IR prednisone (40–60mg) daily for 4 weeks and then randomised to 2 open arms of tapering GC with either standard IR prednisone or MR prednisone. The steroid tapering schedules were identical and the dose was reduced only if disease was controlled by both clinical and laboratory parameters at each visit. Patients were assessed every two weeks for outcome measures, including disease control and flares, GC related and other adverse effects, biomarkers, function (HAQ and patient global VAS), quality of life (EQ5D), and sleep and fatigue scores. Bone density scan was performed at baseline and after 26 weeks. Results: 16 patients were recruited (11 female; mean age 79.6). 10 patients had positive TAB, 4 were negative and 2 samples were insufficient for analysis. 10 patients completed the study and are included in this interim analysis; 4 withdrew (1 in MR group, 3 in IR) and 2 patients remain active in the study. At 26 weeks, 5/6 patients taking MR prednisone were in persistent control, compared to 3/4 receiving IR prednisone. There were no statistically significant differences between the groups in terms of reduction in inflammatory markers, and HAQ, VAS, EQ5D and fatigue scores. EQ5D scores were noted to increase in both groups during the study. Cumulative steroid dosages, weight change and DEXA scores were also not statistically different. Patients on MR prednisone, however, reported significantly poorer sleep scores from week 10 to the end of the study. There were 4 SAEs (2 episodes of sepsis requiring admission and 2 osteoporotic fractures), all in the standard IR prednisone group. Conclusions: MR prednisone appears to be a safe and effective treatment for GCA with a similar outcome profile to standard GC. Its use may be limited by adverse effects on sleep. Larger studies on MR prednisone are required. Acknowledgements: This study was funded by Napp Pharmaceuticals Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3887